Conversor elevador de tensão flyback intercalado aplicado à conexão entre fontes de energias renováveis e um microgrid CC - Scortegagna, Renato Gregolon (2015)
The power demand worldwide is increasing and there is also a growing challenges of integrating different ways of power generation with the DC microgrids. The sources of distributed generation formed by renewable sources such as solar, small wind power plants, fuel cells, among others, usually produce low voltages, leaving the converter provide the voltage gain that enables to their connection to the system. This work presents the study of interleaved flyback converter with focus on mathematical analysis and implementation of the flyback coupled inductor in order to minimize losses. Initially, it made a review of DC-DC converters that have similar application characteristics to the proposal of this work. From the review, the advantages and disadvantages of using isolated converters and their limitations on the power and operating modes are presented. A detailed analysis using the PWM transformer method is performed for determining the voltage gain and the interleaved flyback converter efficiency operating in discontinuous conduction mode. Coupled inductor design procedures and electronic circuit components are presented and detailed. The regenerative and dissipative (RCD) snubbers circuits are designed and implemented to compare the results. A interleaved flyback converter with nominal power of 500 W was simulated and implemented, and simulation and experimental results are presented, compared and discussed. At the end of the work, a DC mainframe is proposed and simulated, making the integration and control of two DC-DC converters operating in parallel.